(untitled) (Comprehensive Journal of Science, 2025)
This study was conducted at the Dialysis Center at Sabratha Teaching Hospital from January to March 2025. The random sample consisted of 51 patients visiting the dialysis department. The study aimed to determine the extent to which chronic diseases such as heart disease, diabetes, high blood pressure, asthma, rheumatism, and kidney cysts affect the development of kidney failure. Statistical results showed that the most prevalent conditions among patients were high blood pressure and diabetes accompanied by high blood pressure, accounting for 17.6% of each, followed by kidney cysts, accounting for 13.7%. The percentage of patients without any chronic disease was 31.4%. These results indicate that blood pressure and diabetes are the most common risk factors for chronic kidney failure requiring dialysis. Comparisons between patients with different chronic diseases revealed no significant differences between groups